Charge transport in poly(3-methylthiophene) schottky barrier diodes - Gomes, Henrique L. (2015)
Schottky-barrier devices were formed from electropolymerised films of poly (3-methylthiophene) (PMeT). Thermal annealing of a partially undoped film led to diodes with rectification ratios as high as 5900 at 1 V and 50,000 at 2.5 V and ideality factors slightly above 2. The temperature dependence of ac loss tangent and forward currents are identical suggesting that bulk effects dominate device behaviour event at very low forward voltages. Below 250 K forward currents are essentially independent of temperature. Preliminary TSC measurements show the presence of at least two trapping levels in the devices. © 1993.